Fabrication procedure and performance of 3D printed X-band horn antenna - Wirth, Sebastian G.; Morrow, Ivor L.; Horsfall, Ian (Institution of Engineering and Technology (IET), 2019)
This paper presents the design, fabrication and performance of fusion deposition modeled 3D printed X-band horn antennas. The WR90 waveguide feed and pyramidal horn flare are printed as one piece from Acrylonitrile Butadiene Styrene (ABS). Different metallisation techniques are assessed to provide a uniform 40 micron coat on the ABS surfaces. Uniquely, the coaxial waveguide launcher is integrated with the waveguide section in a single interference fit operation. The measured and simulated radiation patterns showed good correlation and the antenna return loss was ≤−10dB over the 8.212.4GHz operating range. The measured and simulated antenna gain was in good agreement and increased monotonically from 10–17 ± 1.0dBi across the operating frequency.
Keywords: coating techniques; microstrip antennas; antenna radiation patterns; metallisation; coating techniques; microstrip antennas; antenna radiation patterns; metallisation; antenna feeds; horn antennas; coaxial waveguides; three-dimensional printing